Etika Mencari Ilmu dalam Islam : (Kajian Interdisipliner; Pendekatan Psikologis – Sosiologis) - Nurul Hidayah; Syamsurizal Yazid; Hikmatulloh Hikmatulloh (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Islam encourages its followers to seek knowledge as an obligation that has the value of worship. In Islam, seeking knowledge not only contains academic aspects but also involves psychological and sociological dimensions. This study aims to explore the ethics of seeking knowledge in Islam and examine its psychological-sociological dimensions. This study uses a qualitative method with a literature study approach. Data were obtained from the Qur'an, hadith, journals, and related literature. Data analysis was carried out using the Miles, Huberman, and Saldana models, including data condensation, data presentation, and drawing conclusions. The results of the study show that Islam teaches various ethics in seeking knowledge, such as sincerity, respecting teachers, maintaining intentions, and practicing the knowledge gained. From a psychological perspective, the ethics of seeking knowledge are related to motivation, such as Maslow's hierarchy of needs theory, which explains that achieving knowledge is a human need towards self-actualization. From a sociological perspective, Durkheim's theory highlights the importance of social norms in maintaining balance and harmony in the education process. This study confirms the relevance of the ethics of seeking knowledge in shaping the character of individuals who are faithful, knowledgeable, and moral in the modern era.